1982
DOI: 10.1017/s0033291700055628
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vanadium concentration in manic-depressive illness

Abstract: SYNOPSIS133 samples of plasma taken from 9 normal control and 8 manic-depressive subjects were analysed for vanadium by atomic absorption spectrometry. Mean plasma vanadium concentrations were 0·15 μM in normal control, 0·34 μM in manic and 0·28 μM in depressed subjects, and 0·23 μM in manic-depressive subjects after recovery. The differences between normal subjects and manic and recovered subjects were statistically significant. Significant negative correlations were found between plasma vanadium concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1983
1983
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…There are difficulties in measuring concentrations of trace elements in body tissues, due to the relative insensitivity of some of the available techniques, and there are disagreements about the adequacy of the measures used in some of these studies. Dick et al (1982) showed an increased concentration of vanadium in the plasma of both manic and depressed patients compared with normal controls. Other workers have confirmed some of these findings (Conri et al, 1986a), but Conri et af.…”
Section: The Effect Of Vanadium On the Sodium Pumpmentioning
confidence: 93%
“…There are difficulties in measuring concentrations of trace elements in body tissues, due to the relative insensitivity of some of the available techniques, and there are disagreements about the adequacy of the measures used in some of these studies. Dick et al (1982) showed an increased concentration of vanadium in the plasma of both manic and depressed patients compared with normal controls. Other workers have confirmed some of these findings (Conri et al, 1986a), but Conri et af.…”
Section: The Effect Of Vanadium On the Sodium Pumpmentioning
confidence: 93%
“…Three studies report raised vanadium levels in manicdepressive patients, compared with normal controls (Dick et al, 1982;Naylor et al, 1984;Conri et al, 1986), whereas Ali et al (1985) found no differences in vanadium levels between depressed patients and normal controls. Moreover, Dick et al (1982) found significant differences in vanadium concentrations only between normal controls and manic patients, but not between depressed patients and controls. Recently, Naylor et al (1987) found t h a t vanadium concentration decreased significantly with recovery of depressive psychosis.…”
Section: T H E Clinical Role Of Vanadiummentioning
confidence: 99%
“…Only one main mechanism has been postulated so far: Raised vanadium levels are believed to inhibit the 'sodium pump' leading to an increase in intracellular 'residual sodium' (Dick et al, 1980). How the increase in 'residual sodium' is associated with manic-depressive illness has previously been discussed by Coppen et al (1966).…”
Section: Proposed Mechanism For the Action O F Vanadiummentioning
confidence: 99%
“…Some estimations of tissue concentrations of vanadium have been in the range of the Ki for inhibition of Na-K ATPase and it has been suggested that control of Na-K ATPase and hence membrane transport might be brought about by vanadium. Dick et al (1982) reported that the mean plasma vanadium concentrations of a manic and of a depressed group were significantly higher than that of a normal control group.…”
mentioning
confidence: 95%
“…Although it has its critics, it has been argued that hair is the best tissue to sample to estimate trace metal status in man (Laker, 1982). Dick et al (1982) also reported that, in a group of short cycle manic depressives, there was a significant negative correlation between plasma vanadium concentration and erythrocyte Na-K ATPase activity. In contrast MacDonald et al (1982) found no correlation between the vanadium content of washed erythrocyte membranes and Na-K ATPase activity, but this was a cross sectional inter subject study, i.e.…”
mentioning
confidence: 99%